Efficient Feeding of Molted Hens with Different Feeding and Formulation Methods - Ahmad, Hafiz Anwar; Roland Sr., David A. (International Journal of Poultry Science, 2003)
An experiment was conducted to determine the effect of feeding method (constant vs. variable) and method of formulation (lysine vs. protein) on the performance and profits of molted Dekalb Delta hens from 86 to 94 wk of age as influenced by egg and feed prices. Treatments 1 to 5 were formulated based on lysine to contain 0.69 to 0.57% TSAA and fed continuously regardless of feed consumption (constant feeding). Treatments 6 to 10 were formulated based on lysine to supply 650 to 570 mg TSAA and treatments 11 to 15 were formulated base on protein to supply 660 to 580 mg TSAA per hen per d and were fed based on feed intake. Dietary TSAA level had no overall significant effect on feed consumption, egg production, egg weight, mortality, or body weight. Hens fed diets using constant method of feeding had slightly higher egg production than hens fed diets formulated based on lysine or protein using variable method of feeding. However, egg weight, egg specific gravity, and body weight were not different. Two variable feeding methods had no significant effects on feed consumption, egg production, egg weight, egg specific gravity, or body weight. These results demonstrate that there can be no fixed TSAA or protein requirement of molted hens for maximum profits.